Theory-Based Interventions Combining Mental Simulation and Planning Techniques to Improve Physical Activity: Null Results from Two Randomized Controlled Trials - Meslot, Carine; Gauchet, Aurélie; Allenet, Benoît; François, Olivier; Hagger, Martin S. (Frontiers in Psychology, 2016)
Interventions to assist individuals in initiating and maintaining regular participation in physical activity are not always effective. Psychological and behavioural theories advocate the importance of both motivation and volition in interventions to change health behaviour. Interventions adopting self-regulation strategies that foster motivational and volitional components may, therefore, have utility in promoting regular physical activity participation. We tested the efficacy of an intervention adopting motivational (mental simulation) and volitional (implementation intentions) components to promote a regular physical activity in two studies. Study 1 adopted a cluster randomised design students in which participants (n=92) were allocated to one of three conditions: mental simulation plus implementation intention, implementation intention only, or control. Study 2 adopted a 2 (mental simulation vs. no mental simulation) x 2 (implementation intention vs. no implementation intention) randomised controlled design in which fitness centre attendees (n=184) were randomly allocated one of four conditions: mental simulation only, implementation intention only, combined, or control. Physical activity behaviour was measured by self-report (Study 1) or fitness centre attendance (Study 2) at 4- (Studies 1 and 2) and 19- (Study 2 only) week follow-up periods. Findings revealed no statistically significant main or interactive effects of the mental simulation and implementation intention conditions on physical activity outcomes in either study. Despite adopting protocols consistent with previous research, utilizing objective behavioural measures, and having sufficient statistical power, results provide evidence that, in contrast to previous findings, the motivational and volitional components are not effective in changing physical activity behaviour. Future research should focus on the format of the intervention components, test the effects of each component alone and in combination using standardized measures across multiple samples, and systematically explore effects of candidate moderators.